The Vicissitudes of the French Regional Park Model Illustrated through the Life History of the Morvan. (1st November 2012) - Parra, Constanza
Abstract : The diversity of socio-ecological territories on the European continent has led to a differentiation of institutions for nature protection, ranging from strict nature reserves to semi-protected areas designed to revitalise rural territories. This article examines the French regional park model and illustrates its governance distinctiveness through the life history of the Parc Naturel Régional du Morvan. First, the text analyses the challenging role of regional parks, in which environmental protection and socio-economic sustainability, based upon the enhancement of nature-culture heritage, merge. Second, it looks at the Morvan area within the flow of history, from the heyday of its traditional rural economy to the socio-ecological regulation emanating from the diversity of new actors and social claims made on it. And, third, it concludes with comments on the role of regional parks in contemporary societies as wellsprings of a particular socially innovative environmental citizenship founded in a strong nature-culture relationship.